Studi Etnomatematika Pada Motif Batik Troso Jepara Dalam Bentuk Geometri Dua Dimensi - Cahyaningtiyas, Rizky; Malasari, Putri Nur (Universitas Muhammadiyah Palembang, 2023)
This study aims to explore the concept of a flat shape in the troso batik motif, so that this concept can be developed as a teaching material for elementary school students. Data collection techniques through observation, semi-structured interviews, and document archiving. From the results of the study it is shown that many Jepara troso batik motifs can be applied as a medium to introduce mathematical concepts, especially the concept of flat geometric shapes. The geometry concept shown is in the form of flat shapes, such as square, rectangle, triangle, parallelogram, rhombus, kite, and combined plane patterns. The geometric concept found can be used as teaching material in the form of printed, visual, or other teaching materials, adapted to the learning needs of students